Managing Principal Transfers to Improve Junior High School Performance: Evidence from Siantan District, Anambas Islands Regency - Dahrani Dahrani; Nunu Mahnun (MASI Mandiri Edukasi, 2026)
Principal transfers are a common phenomenon in the Indonesian education system and have significant implications for school management and performance. In this study, school performance refers specifically to teacher performance, learning quality, work discipline, and the effectiveness of program implementation. This study aims to analyze the impact of principal transfers on strategic planning, human resource management, and teacher performance at junior high schools in Siantan District, Anambas Islands Regency. This research employed a qualitative case study approach conducted at SMPN 5 Bukit Tambun and SMPN 2 Siantan. Participants consisted of 2 principals, 12 teachers, and 4 administrative staff selected purposively. Data were collected through observation, in-depth interviews, and document analysis, and were analyzed using data reduction, categorization, and thematic analysis techniques. The findings indicate that principal transfers can generate positive changes, including the development of a more adaptive vision and mission, the strengthening of a work-discipline culture, and more systematic teacher performance management. Transfers also enhance teacher motivation through structured supervision, professional development activities, and increased stakeholder participation. These improvements contribute to better instructional quality and more organized program implementation. However, excessively frequent transfers risk disrupting the continuity of long-term school programs. Therefore, principal transfers should be implemented selectively and strategically, with clear planning and minimum tenure policies to ensure leadership stability and protect the sustainability of long-term educational programs while still promoting school improvement